2017
DOI: 10.4314/tjpr.v16i8.14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of taurine and coenzyme Q10 and their combination against acrylamide-induced oxidative stress in rats

Abstract: Purpose: To clarify the protective effects of Taurine (TA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
5
5
0
2
Order By: Relevance
“…Treatment with CoQ10 revealed a significant decrease in testicular and hepatic MDA levels and a significant increase in testicular and hepatic SOD when compared with the DOX group. These results are accordance with the previous study [49]. Saleh et al concluded that the supplementation of CoQ10 significantly ameliorated liver function and hepatic antioxidant defense capacity and attenuated ROS levels [49].…”
Section: The Central Vein (C) At the Center Of Classic Hepatic Lobule And Cords Of Hepatocytes With Large Rounded Vesicular Nuclei (Arrowsupporting
confidence: 93%
“…Treatment with CoQ10 revealed a significant decrease in testicular and hepatic MDA levels and a significant increase in testicular and hepatic SOD when compared with the DOX group. These results are accordance with the previous study [49]. Saleh et al concluded that the supplementation of CoQ10 significantly ameliorated liver function and hepatic antioxidant defense capacity and attenuated ROS levels [49].…”
Section: The Central Vein (C) At the Center Of Classic Hepatic Lobule And Cords Of Hepatocytes With Large Rounded Vesicular Nuclei (Arrowsupporting
confidence: 93%
“…Malondialdehyde (MDA) is a highly reactive three-carbon dialdehyde, generated as a decomposition product of polyunsaturated fatty acids [ 6 , 39 ]. MDA is frequently investigated index of ROS production, which presents a marker of the overall lipid peroxidation degree [ 9 , 14 , 39 ]. Lipid peroxidation was determined in relation to the quantity of MDA in an admitted assay for measuring the degree of oxidative injury and oxidative stress at the cellular level [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…An achievable approach to guard against ROS-induced cellular damage is to enlarge the oxidative protection capability via intake of antioxidants [ 6 ]. Several exogenous antioxidants have been researched in terms of their potential advantages to defend against oxidative injury [ 14 ]. The activity of enzymatic antioxidant systems, including SOD and GSH-PX, could modulate the balance of ROS with antioxidants [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saleh и соавт. [49] на модели повреждения печени после однократного перорального приема акриламида в дозе 15 мг/кг. На этом фоне животные получали коэнзим Q10 в дозе 200 мг/кг/сут перорально.…”
Section: обзоры литературыunclassified
“…В качестве биохимических показателей повреждения печени оценивался уровень ферментов АлАТ, АсАТ, лактатдегидрогиназы, показатели окислительного стресса: уровень восста-новленного глутатиона, малонового диальдегида, миелопероксидазы, а также провоспалительных цитокинов: ИЛ-1B, ИЛ-6, ФНО-альфа. Прием коэнзима Q10 уже через 2 нед достоверно снижал уровень маркеров повреждения печени, уровень провоспалительных цитокинов и показателей окислительного стресса [49].…”
Section: обзоры литературыunclassified